Analisis dan Penyusunan Spesifikasi Persyaratan Pengguna dan Sistem Aplikasi BudayaKerja dengan Pendekatan Rekayasa Balik: Kasus Perusahaan SmartID - Evanta Yudistira; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
BudayaKerja is an application from the SmartID company that aims to provide an assessment of the results of the accumulated performance achievements of Regional Apparatuses in the form of rankings or reports which will be competed as a benchmark for the work culture of each Regional Apparatus. The work culture application was developed without any required documents due to the fast and dynamic needs of policy makers. The researcher conducted an analysis and preparation of the Work Culture application requirements document using a reverse engineering approach. Reverse engineering is an approach used to analyze a component in the system to obtain the relationship between systems. This research produces user requirements documents and system requirements documents that will be used for the process of procuring goods or services within the scope of government. Identification was carried out through three stages, namely interviews, observation and literature study. The identification results will be analyzed to obtain the requirements to be used as a reference in preparing user requirements and system requirements. The user requirements document consists of an introduction, an overview and the needs of each user. The system requirements document consists of an introduction, an overview and specifications for each use case. The user and system requirements documents that have been prepared will be evaluated by checking the conformity of the documents using guidelines from the Software Engineering literature by Ian Sommerville and Use case Modeling by Kurt Bittner and Ian Spence, and examining the character of a good requirements specification consisting of validity, consistency , document completeness, realism and verifiability. User and system requirements documents are evaluated to obtain constructive feedback and produce requirements documents that can be used for the process of procuring goods or services in the government sphere.